Effect of BCCAO Duration and Animal Models Sex on Brain Ischemic Volume After 24 Hours Reperfusion (Bangladesh Journal of Medical Science, 2018)
Background: Literature study shows, there are several variations regarding BCCAO duration and duration of reperfusion after BCCAO that can cause cerebral ischemia. Duration of BCCAO techniques varies between 10 to 30 minutes, while the duration of reperfusion period ranging between 45 minutes to 72 hours. Differences in the duration of occlusion, duration of BCCAO reperfusion and the sex of animal model could lead to different responses to ischemia conditions.Objective. This study aims to determine whether the duration BCCAO and sex of the animal models influences the volume of cerebral ischemia after 24 hours reperfusion.Method: This study uses post-test only study group design. The subjects are 20 female and 20 male Wistar rat that being divided into 8 groups which are male rat with occlusion duration of 5 minutes, 10 minutes and 20 minute, also the female rat with occlusion duration of 5 minutes, 10 minutes, 20 minutes respectively. BCCAO occlusion then followed by 24 hour reperfusion. Rat decapitation and brain extraction are done after reperfusion. Brain tissue sliced into 2 mm size and stained with 0.05% TTC solution for 30 minutes. Ischemic brain volume are being observed using Cavalieri method. Statistical data are being analyzed using One Way Anova.Result: There are significant difference in male rat cerebral ischemia volume between 5 minutes and 10 minutes occlusion (p